2022
DOI: 10.1017/s0007123421000612
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Ambivalent Sexism and its Relationship with Electoral Choice in Britain

Abstract: We investigate the prevalence and correlates of sexism in the British political context, using a measure of ambivalent sexism that distinguishes between hostile and benevolent sexist attitudes. Drawing on original data from two nationally representative online surveys, we find that more than half of the population hold some sexist attitudes and that these are predicted by gender, education, religiosity and authoritarian values. We demonstrate that the most significant division in sexist attitudes within the Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Ideological variables related to political conservatism also predict sexism. In fact, political conservatism has been found to explain more variance in ambivalent sexism than gender 8 . Moreover, in both men and women, hostile sexism is predicted most strongly and consistently by social dominance orientation (a view of the world in which groups of people compete for dominance and superiority), whereas benevolent sexism is most strongly and consistently predicted by right-wing authoritarianism (which stems from perceptions of the world as a dangerous place and reflects a desire for security) 55 , 56 .…”
Section: Predictors Of Ambivalent Sexismmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideological variables related to political conservatism also predict sexism. In fact, political conservatism has been found to explain more variance in ambivalent sexism than gender 8 . Moreover, in both men and women, hostile sexism is predicted most strongly and consistently by social dominance orientation (a view of the world in which groups of people compete for dominance and superiority), whereas benevolent sexism is most strongly and consistently predicted by right-wing authoritarianism (which stems from perceptions of the world as a dangerous place and reflects a desire for security) 55 , 56 .…”
Section: Predictors Of Ambivalent Sexismmentioning
confidence: 99%
“…Research suggests that children 3 , 4 , young people 5 , 6 and adult men and women around the world 7 endorse ambivalent sexism (that is, agree with items that measure both benevolent sexism, such as “women should be protected by men,” and hostile sexism, such as “women seek to gain power by getting control over men.”). Indeed, according to one study, half of the British population holds these attitudes 8 . Ambivalent sexism is therefore a critical factor in shaping girls’ and women’s lives in a variety of social contexts.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 5 I present a tough test to analyse the sensitivity of these null results. A rich literature on the determinants and associations with support for Brexit highlight that, among other characteristics, those individuals who voted Leave are also those most inclined to harbour socially conservative values (Goodwin & Heath, 2016), antiimmigration preferences (Dennison et al, 2020), and also be inclined to hold hostile sexist attitudes (de Geus et al, 2022) This study contributes to the literature on biases in the political science education in two ways. First, it breaks away from the measurement of biases ex-post and tests for their presence ex-ante actual instruction.…”
Section: Resultsmentioning
confidence: 87%
“…Yet, gender bias can operate in more complex ways. For instance, recent survey-based work finds that over half of the UK population harbours sexist beliefs and that the level of bias interacts with partisanship and Brexit attitudes (de Geus et al, 2022).…”
Section: Gender Qualifications and Voter Evaluationsmentioning
confidence: 99%
“…We aim to identify whether women must work harder in office to overcome gender bias in voter attitudes. A wealth of work has identified gender bias in how voters perceive and evaluate women candidates (de Geus et al, 2022;Saha & Weeks, 2022) and a smaller body of work has shown bias towards incumbent politicians (Boussalis et al, 2021). Historically, studies have found that women are less likely to be selected as candidates for office (Norris & Lovenduski, 1995), and, upon running, were less likely to win than men (Fox & Oxley, 2003;Lawless, 2004).…”
Section: Hypothesesmentioning
confidence: 99%